2006
DOI: 10.1111/j.1600-0625.2006.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits proliferation of human epidermoid carcinoma A431 cells by modulating MEK1 and AP‐1 signalling pathways

Abstract: :  Resveratrol (trans‐3,4′,5‐trihydroxystilbene) is a naturally occurring polyphenolic phytoalexin found in grapes, and has been shown to inhibit the growth of various types of cancer cells. We investigated the mechanism of the antiproliferative effect of resveratrol in A431‐transformed keratinocytes harbouring mutant p53, and show that it is accompanied by G1 cell cycle arrest, which coincides with a marked inhibition of G1 cell cycle regulatory proteins, including cyclins A and D1 and cyclin‐dependent kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 37 publications
8
65
1
Order By: Relevance
“…In the present study, an MTT assay revealed that after treatment with resveratrol at a concentration of 4 µM or more, QGY-7701 viability decreases significantly. The cytotoxicity of resveratrol has been previously evaluated in different cell lines, such as U20S (human osteosarcoma cell line) (Liu et al, 2012), 786-0 (human renal cancer cell line) (Yang et al, 2011), and A431 (human epidermoid carcinoma cells) (Kim et al, 2006). The results of these studies indicate that resveratrol indeed has cytotoxicity.…”
Section: Discussionsupporting
confidence: 56%
“…In the present study, an MTT assay revealed that after treatment with resveratrol at a concentration of 4 µM or more, QGY-7701 viability decreases significantly. The cytotoxicity of resveratrol has been previously evaluated in different cell lines, such as U20S (human osteosarcoma cell line) (Liu et al, 2012), 786-0 (human renal cancer cell line) (Yang et al, 2011), and A431 (human epidermoid carcinoma cells) (Kim et al, 2006). The results of these studies indicate that resveratrol indeed has cytotoxicity.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, the cytotoxic potential of resveratrol towards skin cells is at present unclear. However, while evidence exists to suggest an antiproliferative activity of this compound on certain types of skin cells in vitro (26)(27)(28), data generated from in vivo studies have not been as conclusive (29).…”
mentioning
confidence: 99%
“…The p38 MAPK signaling pathway allows cells to interpret a wide range of external signals and respond appropriately by generating a plethora of different biological effects (30). Phosphorylation and activation of p38 kinase is related to a cellular stress condition and its activity contributes to the regulation of growth arrest, differentiation and apoptosis in response to a variety of cellular stresses (31,32). Previously, UVA-induced GJIc down-regulation in human keratinocytes has been reported to be involved in p38 activation-dependent cx43 phosphorylation and degradation (19).…”
Section: Discussionmentioning
confidence: 99%